Species richness and evenness respond to diverging land‐use patterns – a cross‐border study of dry tropical woodlands in southern Africa. (13th July 2016) - Revermann, Rasmus; Wallenfang, Johannes; Oldeland, Jens; Finckh, Manfred
Abstract: Cross‐border studies offer unique situations to study the impact of different land‐use regimes on ecosystems. Along the Angolan and Namibian border formed by the Okavango River, the environmental conditions and traditional land‐use practises are the same on either side of the river. However, decades of civil war in Angola led to a stagnant development while political stability in Namibia fostered a recent socio‐economic transformation. We investigated the impact of spatially diffuse land use on plant diversity of the dry tropical woodlands covering the vast, sandy hinterlands of the river. As accessibility is the major factor governing land use, we used distance to road as a proxy for land‐use intensity. Based on 58 vegetation plots sized 20 m × 50 m, we showed that species richness increased with distance to road in Angola while in Namibia it remained constant on a lower level. Evenness showed an inverse pattern to species richness and Shannon diversity index showed no response. Analysing diversity patterns according to life forms revealed that these patterns are primarily driven by woody species. The study showed that spatially diffuse land use has a measurable effect on plant diversity and illustrates that roads act as vectors of change.